The digital aspects of the wellbeing of university teachers - Buda, András; Kovács, Klára (Frontiers in Education, 2024)
Introduction: In the past few decades more and more studies have put the mental health and well-being of university lecturers in the limelight, especially considering the fact that lecturers’ scope of responsibilities have been significantly transformed and expanded as a result of the massification and diversification of and structural changes in higher education. These changes intensified the workload, already rather high, thus negatively affecting lecturers’ well-being. It is worth investigating how the increasingly marked presence of digital technologies affects the characteristics of teachers’ workload. In this study, we intend to investigate the impact of digitisation on the various areas of workload and work activities of university lecturers at a large university with many faculties, on the one hand, and teachers of institutions teaching in minority languages, on the other. Methods: The online questionnaire compiled and based on the findings of our previous qualitative study was completed by teachers at one of Hungary’s biggest universities, the University of Debrecen, and lecturers at other institutions of higher education providing for the Hungarian ethnic minority across borders and affiliated with the University of Debrecen, altogether 596 people. The database created obtaining the data was named Central and Eastern European Teachers in Higher Education (CEETHE 2023), IBM SPSS 29 software was used to analyse the data. Results: Digital technology plays a basic role in lecturers’ work. Its importance is shown by the fact that the majority of respondents (54%) experiences significant or very severe stress in connection to technological problems. The majority of time spent with digital devices is included in working hours, so these technologies play a prominent role in dissolving the boundaries between professional and private life. Furthermore, many people find their use more exhausting than mental work performed without relying on them. Conclusion: By continuously developing the digital competency of university lecturers it is possible to mitigate the stress triggered by technological problems as well as reduce screen time. It is necessary to ensure that institutions of higher education introduce policies that ensure work-life balance for teachers.